New data on the scale insects (Hemiptera, Coccoidea) of Tenerife, Canary Islands - Ben-Dov, Yair (2013)
This short communication presents new data on 16 species of scale insects, belonging to 5 families of the Coccoidea (Hemiptera) which were collected by the author on April 1995 in the course of a short visit to Tenerife Island. Three species, indicated below with an asterisk *, are recorded here for the first time from the Canary Islands. Slide-mounted specimens of all the species recorded here are deposited in the Coccoidea Collection, Department of Entomology, Agricultural Research Organization, Bet Dagan, Israel. The collection number of each record is indicated in the Material Examined section.